Nuevos acercamientos a los estudios latinoamericanos : cultura y poder (Universidad Nacional Autónoma de México ; CLACSO, 2021)
This volume makes a cartography of the last twenty-five years of the field of Latin American studies organized by turns. Its sixteen chapters, which range from the turn of memory, the decolonial, the transatlantic, to the affective, include both a review of the key bibliography to understand the respective paradigm shift and its effects on the broader field of Latin American studies, as well as an evaluation of the achievements, possibilities and limitations of the mutation studied. Through a broad panorama, although not exempt from controversies or controversies, of the radical transformation of the themes, problems, scope and epistemological and methodological assumptions of the field in that period, it suggests some paths for the immediate future.